2021
DOI: 10.3390/en14164795
|View full text |Cite
|
Sign up to set email alerts
|

Do People Prefer Cars That People Don’t Drive? A Survey Study on Autonomous Vehicles

Abstract: Only recently, smart cities are taking shape, thanks to the rapid development of Internet of Things (IoT), cloud computing, and other similar technologies. Given the high demands placed on advanced technologies such as autonomous driving, cloud data services, and high-precision sensors, smart cities are creating an intelligent transportation environment conducive to the introduction of autonomous vehicles (AVs). In this context, the use of AVs in transportation is also considered a form of transportation innov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…Huang (2023) [65] investigated the psychological factors affecting users and found that potential users' intentions to use autonomous vehicles and usability and technology acceptance model are important factors. Additionally, Meidute-Kavaliauskiene et al (2021) [69] conducted a survey study on autonomous vehicles, finding that younger respondents with a tech-savvy background were more likely to have a positive attitude towards autonomous vehicles. Additionally, Erskine et al [70] applied the unified theory of technology acceptance and use (UTAUT2) to evaluate consumer attitudes and behavioral intentions towards autonomous vehicles.…”
Section: Literature Review Research Model and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Huang (2023) [65] investigated the psychological factors affecting users and found that potential users' intentions to use autonomous vehicles and usability and technology acceptance model are important factors. Additionally, Meidute-Kavaliauskiene et al (2021) [69] conducted a survey study on autonomous vehicles, finding that younger respondents with a tech-savvy background were more likely to have a positive attitude towards autonomous vehicles. Additionally, Erskine et al [70] applied the unified theory of technology acceptance and use (UTAUT2) to evaluate consumer attitudes and behavioral intentions towards autonomous vehicles.…”
Section: Literature Review Research Model and Hypothesesmentioning
confidence: 99%
“…Some studies in the literature were conducted by evaluating technological readiness [14,38,69,91] as well as consumers' gender and age variables. Based on the literature review, the research model and research hypotheses were detailed and created as shown in Figure 2 below.…”
Section: The Effect Of Attitude Towards Use On Intention To Usementioning
confidence: 99%